2 - Institutionalised Marginality, Social Conflicts and the Quest for National Unity in an African Nation-State: A Theoretical Exploration: 10.4314/ad.v28i2.22175 - Ujomu , Philip Ogo (Africa Development, 2003)
This essay focuses on the issue of marginality, marginalisation and the quest for national unity. Although, the issue of marginalisation in a nation-state such as Nigeria has been widely discussed by writers, few have attempted to offer a systematic analysis of the issue through a theoretical or conceptual basis. This paper examines the extent to which the competition for resources and the exer cise of political control have compelled the marginalisation of various segments of Nigerian society. It highlights the evolving nature and different expressions of marginalisation. By looking at the issue of marginality and the social order in Nigeria against the backdrop of the brutal facts of injustice, inequality and exploitation, we seek to discern the epochal configurations and socio-cultural locations of the problem. Our aim is to discover how this problem has militated against the quest for national integration and reconciliation in the polity. And by highlignting the attendant crisis of social order occasioned by marginalisation, this essay reinforces the need for the urgent establishment of enduring humane rules of distributive justice in the society.